Treatment with corticosteroids is associated with an increase in ventricular arrhythmia burden in patients with clinically manifest cardiac sarcoidosis: Insights from implantable cardioverter‐defibrillator diagnostics. (4th August 2020) - Medor, Maria C.; Spence, Stewart; Nery, Pablo B.; Beanlands, Rob; Promislow, Steven; Juneau, Daniel; de Kemp, Rob; Ha, Andrew C.; Rivard, Lena; Gula, Lorne; Birnie, David H.
Abstract: Introduction: We sought to explore the relationship between ventricular tachycardia (VT) and premature ventricular complex (PVC) burden (from implantable cardioverter‐defibrillator diagnostics), before and during corticosteroid use in patients with newly diagnosed clinically manifest cardiac sarcoidosis (CS). Methods: A single‐centre, prospective cohort study was performed in consecutive patients who met all of the following criteria: (1) presentation with clinically manifest CS, (2) abnormal myocardial fluoro‐deoxyglucose (FDG) uptake on positron emission tomography scan, (3) plan for implantation with implantable cardioverter‐defibrillator device that reports accurate PVC count, (4) plan to initiate corticosteroids after the device healing period. Data were collected during each device interrogation visit for all patients in the study. For each inter‐visit period the total number of episodes of VT—sustained and nonsustained, and the number of PVCs was obtained. Each inter‐visit period was classified into one of the following three periods: (1) New diagnosis of treatment‐naive active disease without corticosteroids during the period. (2) Known treatment‐naive active disease with corticosteroids initiated during the inter‐visit period. (3) On corticosteroid therapy during the entire period. Results: A total of 20 patients with a mean age of 59.7 ± 7.7 years were recruited and 82 inter‐visit periods were analyzed. All patients were corticosteroid responders based on FDG uptake. The maximum left ventricular standardized uptake value was 11.14 ± 5.19 before corticosteroid initiation and 4.07 ± 0.88 after ( p < .001). Patients with active untreated CS had an average of 496.4 ± 879.1 PVCs per day. After treatment with corticosteroids, the average PVC count increased to 1332.4 ± 1865.7/day during Period 2 ( p = .036) and to 1590.1 ± 2362.2 per day during Period 3 ( p = .008). There was also a statistically significant increase in episodes of nonsustained ventricular tachycardia (NSVT) before and after treatment with corticosteroids ( p = .017). There were too few episodes of sustained ventricular arrhythmia to analyze. Overall, 18 out of 20 patients (90%) had an increase in PVC burden after corticosteroid initiation. Conclusion: This study demonstrated, on average, a threefold increase in daily PVC count in clinically manifest CS patients during treatment with corticosteroids compared to pretreatment. There was also a significant increase in episodes of NSVT. Clinicians and patients with active manifest CS should be aware that corticosteroids are unlikely to lead to a reduction in the burdens of PVC and NSVT.